PUBLIC ADMINISTRATION IN EUROPEAN REGIONAL DEVELOPMENT MODELS: EXPERIENCE FOR UKRAINE - Kovalchuk V.H. (Pressing Problems of Public Administration, 2015)
The features of public administration of regional development in the EU member states areconsidered. The basic principles of state regional policy in the modern world have beenresearched. The analysis has been conducted as to the trends of implementing the Europeanpractices of social and economic processes regulation in Ukraine.